Self-repairing anti-interference film and preparation method and application thereof
By using a self-healing anti-interference film layer with two layers of electrical polymerization film in the glucose sensor, and using the combination of anti-interference monomer and comonomer, the interference and complexity problems of traditional anti-interference film layers in the glucose sensor are solved, and the interference and complexity of traditional anti-interference film layers in the glucose sensor is achieved. Efficient self-healing and anti-interference simplify manufacturing and use processes.
Patent Information
- Application Number
- CN202411322571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-15
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-13
AI Technical Summary
Existing glucose sensors show serious interference problems when detecting interference from electrochemical active substances in the blood. The traditional anti-interference film layer is difficult to control the film thickness, which increases process complexity and cost, and requires regular repair, affecting the manufacturing and use of the instrument.
A self-healing anti-interference film layer is designed. Through the combination of two layers of electrical polymerization films, anti-interference monomers such as ortho-phenylenediamine and acetaminophen are used to form a dense anti-interference film that can be used in work. Self-healing in the state, blocking interfering objects in the blood and maintaining the anti-interference of the sensor.
It realizes that without adding complex repair procedures to the terminal, simplifies the instrument manufacturing process, reduces costs, and provides good process reproducibility and lasting anti-interference performance, ensuring the stability of the sensor within 30 days.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] This application claims the priority of the Chinese patent application filed with the China Patent Office on May 15, 2024, with application number 202410608562.8 and invention name “Composition, anti-interference membrane and its application”, the entire contents of which are incorporated by reference in this application. Technical Field
[0002] The present invention relates to the field of biological detection, and in particular to a self-repairing anti-interference membrane and a preparation method and application thereof. Background Art
[0003] Glucose is one of the most direct sources of energy in the human body, and its concentration in the blood is often used as one of the evaluation indicators of human health status and clinical diagnosis. The determination of glucose is of great significance for the management of human health status and clinical diagnosis and treatment. At present, enzyme electrode sensor detection is the main method for glucose detection. The general principle is that the glucose in the sample generates gluconic acid and hydrogen peroxide under the catalysis of glucose oxidase in the enzyme membrane, and hydrogen peroxide generates a current signal under constant potential. The current signal can be linearly related to the glucose concentration in the sample within a certain range.
[0004] Electrochemically active substances in the blood, such as acetaminophen, uric acid, ascorbic acid, etc., will undergo redox reactions at potentials lower than the working potential to generate electrical signals, thus causing serious interference to such sensors.
[0005] Related researchers have coated an additional anti-interference membrane on the innermost layer of the electrode to reduce interference, such as cellulose acetate membrane. Since glucose sensors are generally microelectrode wires, this solution makes it difficult to control the membrane thickness, increases the complexity of the process, and has poor batch-to-batch reproducibility. Other researchers use electropolymerization to make anti-interference layers, such as using monomers containing electroactive groups such as thiophene, carbazole, and triphenylamine for electropolymerization. The molecular structure of this type of polymer film layer will gradually be destroyed during operation, and monomers need to be regularly replenished for electropolymerization repair. In practical applications, this will significantly complicate the instrument manufacturing process and increase costs. Summary of the invention
[0006] In view of this, the present invention provides a self-repairing anti-interference film and a preparation method and application thereof. The present invention designs a self-repairing anti-interference film layer, which completes electropolymerization at one time before leaving the factory. The complexity of the instrument and the process cost are reduced, and there is no subsequent repair procedure to occupy and exclude the user's use. In addition, compared with the coating method, electropolymerization can form an ideal film thickness by controlling the monomer concentration, electropolymerization parameters, etc., and the process reproducibility is good.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a composition, comprising: an anti-interference monomer and an interferent comonomer;
[0009] The anti-interference monomer includes: any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine;
[0010] The interfering substance comonomer includes: acetaminophen.
[0011] In some embodiments of the present invention, in the above composition, the anti-interference monomer is o-phenylenediamine; and the interferer comonomer is acetaminophen.
[0012] In some embodiments of the present invention, in the above composition, the molar ratio of the anti-interference monomer to the interferer comonomer is 1:1.
[0013] The present invention also provides application of the composition in preparing an anti-interference membrane in a blood glucose sensor.
[0014] The present invention also provides an anti-interference film, comprising: a first electropolymer film and a second electropolymer film;
[0015] The first electropolymer film comprises: the anti-interference monomer in the above composition; specifically, the first electropolymer film is formed by the anti-interference monomer in the above composition;
[0016] The second electropolymer film comprises: the anti-interference monomer and the interferer co-monomer in the above combination; specifically, the second electropolymer film is formed by the anti-interference monomer and the interferer co-monomer in the above composition.
[0017] In some embodiments of the present invention, in the above-mentioned anti-interference film, the anti-interference monomers in the first electropolymer film and the second electropolymer film are the same.
[0018] In some embodiments of the present invention, in the above-mentioned anti-interference membrane, in the first electropolymer membrane and the second electropolymer membrane, the concentration of the anti-interference monomer is 60-70 mM;
[0019] In the second electropolymerized membrane, the concentration of the interfering comonomer is 60-70 mM.
[0020] In some embodiments of the present invention, in the above-mentioned anti-interference membrane, in the first electropolymeric membrane and the second electropolymeric membrane, the concentration of the anti-interference monomer is 60mM or 70mM;
[0021] In the second electropolymerized membrane, the concentration of the interferent comonomer is 60 mM or 70 mM.
[0022] The present invention also provides a method for preparing the above-mentioned anti-interference membrane, wherein the first electropolymer membrane and the second electropolymer membrane are electropolymerized to an electrode system respectively to obtain the anti-interference membrane.
[0023] In some embodiments of the present invention, in the above preparation method, the potential of the electropolymerization is 600 mV and the time is 10 min.
[0024] In some embodiments of the present invention, in the above preparation method, the electrode system includes: a working electrode, a counter electrode and a reference electrode.
[0025] The present invention also provides the use of the anti-interference film and / or the anti-interference film obtained by the above preparation method in the preparation of a blood glucose sensor.
[0026] The present invention also provides a blood glucose sensor, comprising: the above-mentioned anti-interference membrane and / or the anti-interference membrane obtained by the above-mentioned preparation method.
[0027] In some embodiments of the present invention, the blood glucose sensor further includes: an enzyme layer and an outer layer.
[0028] Specifically, the blood glucose sensor comprises: an electrode, a first electropolymer film disposed on the electrode, a second electropolymer film disposed on the first electropolymer film, an enzyme layer disposed on the second electropolymer film, and an outer layer disposed on the enzyme layer;
[0029] The first electropolymer film is formed by an anti-interference monomer; the anti-interference monomer includes: any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine;
[0030] The second electropolymerized film is formed by an anti-interference monomer and an interferer comonomer; the anti-interference monomer includes any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine; the interferer comonomer includes acetaminophen.
[0031] In some embodiments of the present invention, in the above blood glucose sensor, the anti-interference monomers in the first electropolymeric film and the second electropolymeric film are the same.
[0032] In some embodiments of the present invention, in the above-mentioned blood glucose sensor, in the second electropolymer film, the molar ratio of the anti-interference monomer to the interferer comonomer is 1:1.
[0033] In some embodiments of the present invention, in the above blood glucose sensor, the enzyme layer includes: glucose oxidase: 10%, bovine serum albumin: 10%, polyvinyl pyrrolidone: 1%, glutaraldehyde: 1% and 0.02 mol / L phosphate buffer: 78%.
[0034] In some embodiments of the present invention, in the above-mentioned blood glucose sensor, the outer layer comprises: polyurethane: 4%, polyvinyl chloride: 1% and pyridine: 95%.
[0035] The present invention provides a composition, comprising: an anti-interference monomer and an interferent comonomer;
[0036] The anti-interference monomer includes: any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine;
[0037] The interfering substance comonomer includes: acetaminophen.
[0038] The present invention provides a method for preparing a self-repairing anti-interference film layer of a blood glucose sensor, specifically, the method comprises two layers of electropolymerized anti-interference layers, the first layer is a common electropolymerized anti-interference layer, and the second layer is a more dense copolymer anti-interference layer.
[0039] When the sensor is measuring the sample, the two layers of anti-interference membrane block the small molecular active interferents in the blood outside the electrode, so that they cannot generate interference signals. In the working state, the molecular structure of the anti-interference membrane layer can self-repair to ensure that the sensor has anti-interference performance during its service life (30 days). The self-repair working principle is as follows:
[0040] The present invention also provides a method for preparing the above blood glucose sensor, comprising the following steps:
[0041] S1) sequentially forming the first electropolymer film and the second electropolymer film on the electrode to obtain an electrode provided with a self-repairing anti-interference film;
[0042] S2) forming an enzyme layer and an outer layer in sequence on the electrode obtained in step S1) to obtain the blood glucose sensor.
[0043] The present invention first forms the second electropolymer film and the first electropolymer film on the electrode in sequence to obtain an electrode provided with an anti-interference film; specifically, the second electropolymer film and the first electropolymer film are formed in sequence on the electrode by electropolymerization, and the electropolymerization potential is 600 mV and the time is 10 min. In certain embodiments of the present invention, the electrode is immersed in a sodium acetate buffer of the above-mentioned anti-interference monomer, and electropolymerization is performed at a potential of 600 mV for 10 min using a chronoamperometry to form the second electropolymer film on the electrode; the obtained electrode is then immersed in a sodium acetate buffer of the above-mentioned anti-interference monomer and the above-mentioned interfering comonomer, and electropolymerization is performed at a potential of 600 mV for 10 min using a chronoamperometry to obtain an electrode provided with an anti-interference film;
[0044] After obtaining an electrode provided with an anti-interference membrane, the present invention sequentially forms an enzyme layer and an outer layer on the obtained electrode to obtain the blood glucose sensor. Specifically, an immobilized enzyme solution is dripped on the electrode provided with an anti-interference membrane, and the enzyme layer is formed after natural drying, and finally a polyurethane solution is dripped on the electrode provided with an anti-interference membrane, and the outer layer is formed after natural drying.
[0045] When the sensor is working, the monomers in the electropolymerized anti-interference film layer are continuously and slowly lost. However, in clinical samples, the patient's blood may contain various interferences. Since the working potential of the sensor of the present invention is the same as the electropolymerization potential of the anti-interference film layer (600 mV), when the interference acetaminophen enters the surface of the second anti-interference film layer, the film layer undergoes electropolymerization, and part of the acetaminophen in the sample is supplemented to the monomer position lost in the film layer. At the same time, the monomers in the first anti-interference film layer also have a slight loss. When they diffuse outward, they are intercepted by the second anti-interference film layer. Some monomers continue to undergo electropolymerization on the surface of the second anti-interference film layer and are supplemented to the corresponding monomer position lost in the second film layer. This repairable and dense second anti-interference film layer provides protection for the first anti-interference film layer. Thus, a stable anti-interference system is formed, which provides the sensor with long-lasting and effective anti-interference performance.
[0046] The sensor can complete a one-time anti-interference membrane electropolymerization before leaving the factory, without the need to use a specific electropolymerization solution package at the end and start a complex procedure for regular electropolymerization repair. This greatly simplifies the instrument manufacturing process and reduces costs. It also does not occupy or crowd out clinical testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0048] Figure 1 The CV curve of the second layer of electropolymerization solution is shown in Figure 2. The oxidation peak current at 600 mV decreases gradually with the number of scans, indicating that the second anti-interference membrane layer with poor conductivity is gradually formed, and this oxidation peak potential is the same as the working potential of the glucose sensor.
[0049] Figure 2 The it curve of the electropolymerization of the two anti-interference film layers in Example 1 is shown. The current gradually decreases with the electropolymerization time, indicating that two anti-interference film layers with poor conductivity are gradually formed, and the second film layer is more dense;
[0050] Figure 3 The schematic diagram of the structure of the sensor is shown;
[0051] Figure 4The scanning electron microscope (SEM) image taken after electropolymerization of two anti-interference layers in Example 1 shows that a dense mesh structure has been formed on the platinum wire, and the mesh size is about 100 nm. This structure can effectively prevent active interference substances from entering the electrode surface to generate interference signals;
[0052] Figure 5 This is a graph showing the mean daily blood glucose concentration results of the anti-interference ability test of Comparative Examples 1 to 6 of the present invention;
[0053] Figure 6 This is a graph showing the mean daily blood glucose concentration results of the anti-interference ability test of Examples 1 to 4 of the present invention;
[0054] Figure 7 This is a diagram of the clinical sample simulation results of the present invention. DETAILED DESCRIPTION
[0055] The invention discloses a self-repairing anti-interference film and a preparation method and application thereof.
[0056] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0057] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0058] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0059] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0060] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0061] The present invention provides a method for preparing an anti-interference film layer of a self-repairing blood glucose sensor. Specifically, the method comprises an electropolymerization anti-interference layer, an enzyme layer and an outer layer.
[0062] Among them: the electropolymerization anti-interference layer consists of two layers.
[0063] The first layer of electropolymerized film: preferably o-phenylenediamine (optionally: p-phenylenediamine, m-phenylenediamine); wherein: o-phenylenediamine is electropolymerized to form poly-o-phenylenediamine, and two amino active groups are cross-linked with each other.
[0064] The second layer of electropolymerized film: preferably o-phenylenediamine (when the first layer of electropolymerized monomer is p-phenylenediamine or m-phenylenediamine, the second layer is p-phenylenediamine or m-phenylenediamine) and acetaminophen; wherein: acetaminophen contains two active groups, acetyl and phenolic hydroxyl, which can cross-link with the two active groups of phenylenediamine to form a copolymer. In molecular imprinting, this type of copolymerization is a common structure. The structural formula of acetaminophen is shown below:
[0065] Formula 1.
[0066] After the two layers of anti-interference membranes are electropolymerized onto the working electrode wire (platinum wire) one after another, the immobilized enzyme solution is dripped onto the anti-interference membrane layer to form an enzyme layer, wherein the components of the immobilized enzyme solution are as follows:
[0067] Glucose oxidase: 10%
[0068] Bovine serum albumin: 10%
[0069] Polyvinylpyrrolidone: 1%
[0070] Glutaraldehyde: 1%
[0071] 0.02mol / L phosphate buffer: 78%
[0072] A polyurethane solution is dripped onto the enzyme layer to form an outer layer, wherein the composition of the polyurethane solution is as follows:
[0073] Polyurethane: 4%
[0074] Polyvinyl chloride: 1%
[0075] Pyridine: 95%.
[0076] In Examples 1 to 4, Comparative Examples 1 to 6 and the verification examples of the present invention, all the raw materials and reagents used can be purchased from the market.
[0077] The present invention will be further described below in conjunction with embodiments:
[0078] Example 1
[0079] The first electropolymerized film: 60 mM o-phenylenediamine;
[0080] The second electropolymerized film: 60 mM o-phenylenediamine and 60 mM acetaminophen;
[0081] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 60 mM o-phenylenediamine and 60 mM acetaminophen sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0082] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the enzyme layer is formed after natural drying. Finally, the polyurethane solution is dripped onto the wire, and the outer layer is formed after natural drying, thereby obtaining a blood glucose sensor with stable anti-interference characteristics.
[0083] Example 2
[0084] First electropolymerized film: 60 mM m-phenylenediamine;
[0085] The second electropolymerized film: 60 mM m-phenylenediamine and 60 mM acetaminophen;
[0086] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM m-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 60 mM m-phenylenediamine and 60 mM acetaminophen sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0087] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the enzyme layer is formed after natural drying. Finally, the polyurethane solution is dripped onto the wire, and the outer layer is formed after natural drying, thereby obtaining a blood glucose sensor with stable anti-interference characteristics.
[0088] Example 3
[0089] First electropolymerized film: 60 mM p-phenylenediamine;
[0090] The second electropolymerized film: 60 mM p-phenylenediamine and 60 mM acetaminophen;
[0091] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM p-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 60 mM p-phenylenediamine and 60 mM acetaminophen sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0092] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the enzyme layer is formed after natural drying. Finally, the polyurethane solution is dripped onto the wire, and the outer layer is formed after natural drying, thereby obtaining a blood glucose sensor with stable anti-interference characteristics.
[0093] Example 4
[0094] The first electropolymerized film: 70 mM o-phenylenediamine;
[0095] The second electropolymerized film: 70 mM o-phenylenediamine and 70 mM acetaminophen;
[0096] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 70 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 700 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 70 mM o-phenylenediamine and 70 mM acetaminophen sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 700 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0097] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the enzyme layer is formed after natural drying. Finally, the polyurethane solution is dripped onto the wire, and the outer layer is formed after natural drying, thereby obtaining a blood glucose sensor with stable anti-interference characteristics.
[0098] Comparative Example 1
[0099] The first electropolymerized film: 60 mM o-phenylenediamine;
[0100] Second layer of electropolymerized film: None;
[0101] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM o-phenylenediamine sodium acetate buffer (pH=4.8) and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a layer of electropolymerized film.
[0102] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the solution is naturally dried to form an enzyme layer. Finally, the polyurethane solution is dripped onto the working electrode wire, and the solution is naturally dried to form an outer layer, thereby obtaining a blood glucose sensor.
[0103] Comparative Example 2
[0104] The first layer of electropolymerized film: None;
[0105] The second electropolymerized film: 60 mM o-phenylenediamine and 60 mM acetaminophen;
[0106] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM o-phenylenediamine and 60 mM acetaminophen sodium acetate buffer (pH=4.8) and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a layer of electropolymerized film.
[0107] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the solution is naturally dried to form an enzyme layer. Finally, the polyurethane solution is dripped onto the working electrode wire, and the solution is naturally dried to form an outer layer, thereby obtaining a blood glucose sensor.
[0108] Comparative Example 3
[0109] The first electropolymerized film: 60 mM o-phenylenediamine;
[0110] The second electropolymerized membrane: 60 mM o-phenylenediamine;
[0111] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 60 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0112] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the solution is naturally dried to form an enzyme layer. Finally, the polyurethane solution is dripped onto the working electrode wire, and the solution is naturally dried to form an outer layer, thereby obtaining a blood glucose sensor.
[0113] Comparative Example 4
[0114] The first electropolymerized film: 60 mM o-phenylenediamine;
[0115] The second electropolymerized membrane: 60 mM o-phenylenediamine and 60 mM uric acid;
[0116] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 60 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 60 mM o-phenylenediamine and 60 mM uric acid sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0117] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the solution is naturally dried to form an enzyme layer. Finally, the polyurethane solution is dripped onto the working electrode wire, and the solution is naturally dried to form an outer layer, thereby obtaining a blood glucose sensor.
[0118] Comparative Example 5
[0119] The first electropolymerized film: 40 mM o-phenylenediamine;
[0120] The second electropolymerized film: 40 mM o-phenylenediamine and 40 mM acetaminophen;
[0121] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 40 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 40 mM o-phenylenediamine and 40 mM acetaminophen sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0122] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the solution is naturally dried to form an enzyme layer. Finally, the polyurethane solution is dripped onto the working electrode wire, and the solution is naturally dried to form an outer layer, thereby obtaining a blood glucose sensor.
[0123] Comparative Example 6
[0124] The first electropolymerized film: 80 mM o-phenylenediamine;
[0125] The second electropolymerized film: 80 mM o-phenylenediamine and 80 mM acetaminophen;
[0126] The working electrode platinum wire, the counter electrode platinum wire and the reference electrode Ag / AgCl constituted a three-electrode system, which was immersed in 80 mM o-phenylenediamine sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a first electropolymerized film layer. Subsequently, the three-electrode system was immersed in 80 mM o-phenylenediamine and 80 mM acetaminophen sodium acetate buffer (pH=4.8), and electropolymerized at a potential of 600 mV for 10 min using the chronoamperometry to obtain a working electrode containing a second electropolymerized film layer.
[0127] Subsequently, the immobilized enzyme solution is dripped onto the working electrode wire, and the solution is naturally dried to form an enzyme layer. Finally, the polyurethane solution is dripped onto the working electrode wire, and the solution is naturally dried to form an outer layer, thereby obtaining a blood glucose sensor.
[0128] Example 5 Method of using a blood glucose sensor
[0129] The blood glucose sensors obtained in Examples 1 to 4 and Comparative Examples 1 to 5 were tested with glucose solutions of 0, 3, 6, 9, and 12 mM concentrations, respectively, to obtain the corresponding currents. A graph was drawn with current as the ordinate and concentration as the abscissa, and the fitting curve was calculated as the standard curve of each sensor. When the sample was tested, the sample current was substituted into the fitting curve to obtain the sample concentration.
[0130] Verification Example 1 Performance Test
[0131] Four different test solutions were prepared using glucose quality control solution, and their main components and contents are as follows:
[0132] A: glucose 4 mM;
[0133] B: glucose 4 mM, interfering substance uric acid 1 mM;
[0134] C: glucose 4 mM, interfering substance acetaminophen 1 mM;
[0135] D: glucose 4 mM, interfering substance vitamin C 1 mM;
[0136] The sensor prepared above was used to test the four solutions A, B, C, and D three times each day, and the mean was calculated. According to the National Health Commission Clinical Laboratory Center standard, the accuracy of blood glucose is required to be ±7% of the target value. Therefore, we stipulate that when the calculated mean exceeds 4.28 mM, the anti-interference performance of the sensor is judged to have decayed to the point where it does not meet the requirements. The experimental results are shown in Table 1, and the original results corresponding to Table 1 are shown in Figures 5 and 6As shown, Figure 5 This is a graph showing the mean daily blood glucose concentration results of the anti-interference ability test of Comparative Examples 1 to 6 of the present invention. Figure 6 This is a graph showing the mean daily blood glucose concentration results of the anti-interference ability test of Examples 1 to 4 of the present invention:
[0137] Table 1
[0138]
[0139] The experimental results are shown in Table 1. The anti-interference stability of Comparative Examples 1-2 is poor compared with the embodiment, which indicates that a single layer of electropolymer film cannot form a stable self-repairing function;
[0140] Compared with Comparative Examples 1-2, the anti-interference stability of Comparative Examples 3-4 was not significantly improved, which illustrates the core role of acetaminophen in the embodiment in the self-repair process of the membrane layer;
[0141] The anti-interference stability of Comparative Examples 5-6 is improved compared with Comparative Examples 1-4, but is still worse than that of the embodiment, which shows that the appropriate monomer concentration in the electropolymerization process can form a suitable cross-linking density, which is beneficial to the supplementation and self-repair of acetaminophen, making the anti-interference structure more stable.
[0142] Verification Example 2 Clinical Sample Simulation
[0143] In Verification Example 1, samples containing a high concentration of acetaminophen are tested every day, so that the sensor anti-interference layer membrane self-repairs more fully. However, this is not the case in reality. In clinical practice, a sample containing acetaminophen may be tested occasionally, and the concentration is low. In order to verify the minimum frequency and concentration of acetaminophen samples required for the self-repair of the anti-interference membrane layer of the present invention, we designed the following experiment.
[0144] Test fluid:
[0145] A: glucose 4 mM;
[0146] B: glucose 4 mM, interfering substance uric acid 1 mM;
[0147] C: glucose 4 mM, interfering substance vitamin C 1 mM;
[0148] D: glucose 4 mM, interfering substance acetaminophen 0.05 mM;
[0149] E: glucose 4 mM, interfering substance acetaminophen 0.1 mM;
[0150] F: glucose 4 mM, interfering substance acetaminophen 0.15 mM;
[0151] Test plan:
[0152] Using the four groups of sensors obtained in Example 1 (numbered sensor-1 to sensor-4), the four groups of sensors tested A, B and C test liquids three times each day, where sensor-1 was tested only on this basis and D, E and F test liquids were not tested subsequently, sensor-2 was tested on this basis once every 10 days with D test liquid, sensor-3 was tested on this basis once every 7 days with E test liquid, and sensor-4 was tested on this basis once every 5 days with F test liquid. The average test values of the four groups of sensors were calculated every day. The summary results are as follows: Figure 7 As shown, Figure 7 This is a simulation result diagram of clinical samples of the present invention. Figure 7 The corresponding data are shown in Table 2:
[0153] Table 2
[0154]
[0155] It can be seen from this that the sensor of the present invention only needs to test one case containing at least 0.1 mM acetaminophen within at least 7 days to achieve self-repair function, thereby achieving stable anti-interference performance within 30 days, which has good practical application significance in clinical practice.
[0156] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Self-repairing anti-interference film, characterized in that: include: a first electropolymeric film and a second electropolymeric film; The first electropolymer film is formed of an anti-interference monomer; The anti-interference monomer includes: any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine; The second electropolymerized film is formed by an anti-interference monomer and an interferer co-monomer; the anti-interference monomer includes any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine; the interferer co-monomer includes acetaminophen.
2. The self-repairing anti-interference film according to claim 1, characterized in that: The anti-interference monomers in the first electropolymer film and the second electropolymer film are the same.
3. The self-repairing anti-interference film according to claim 1, characterized in that: In the second electropolymerized film, the molar ratio of the anti-interference monomer to the interferer comonomer is 1:
1.
4. The method for preparing a self-repairing anti-interference film according to any one of claims 1 to 3, characterized in that: The first polymer film and the second electropolymer film are electropolymerized to an electrode system respectively to obtain the self-repairing anti-interference film.
5. A blood glucose sensor, characterized in that include: an electrode, a first electropolymer membrane disposed on the electrode, a second electropolymer membrane disposed on the first electropolymer membrane, an enzyme layer disposed on the second electropolymer membrane, and an outer layer disposed on the enzyme layer; The first electropolymer film is formed by an anti-interference monomer; the anti-interference monomer includes: any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine; The second electropolymerized film is formed by an anti-interference monomer and an interferer co-monomer; the anti-interference monomer includes any one of o-phenylenediamine, p-phenylenediamine and m-phenylenediamine; the interferer co-monomer includes acetaminophen.
6. The blood glucose sensor according to claim 5, wherein: The anti-interference monomers in the first electropolymer film and the second electropolymer film are the same.
7. The blood glucose sensor according to claim 5, wherein: In the second electropolymerized film, the molar ratio of the anti-interference monomer to the interferer comonomer is 1:
1.
8. The blood glucose sensor according to claim 5, wherein: The working potential of the blood glucose sensor is 600mV.
9. The method for preparing a blood glucose sensor according to any one of claims 5 to 8, characterized in that: The following steps are involved: S1) sequentially forming the first electropolymer film and the second electropolymer film on the electrode to obtain an electrode provided with a self-repairing anti-interference film; S2) forming an enzyme layer and an outer layer in sequence on the electrode obtained in step S1) to obtain the blood glucose sensor.
10. The method for preparing a blood glucose sensor according to claim 9, characterized in that: In step S1), the first electropolymer film and the second electropolymer film are sequentially formed on the electrode by electropolymerization, and the potential of the electropolymerization is 600 mV and the time is 10 min.
Citation Information
Cited By
Bio-enzyme electrode, preparation method thereof and wearable electrochemical biosensor
CN120908281A
